Floating Fish Cage Farming a Solution to Uganda’s Declining Fishery Stocks - Mbowa, Swaibu; Odokonyero, Tonny; Munyaho, Anthony T. (Economic Policy Research Centre, 2016)
This brief is extracted from a study on cage culture and aquaculture park technologies in Uganda conducted by EPRC and National Fisheries Resources Research Institute (NaFIRRI). The brief demonstrates that favorable and bullish international fish prices have supported steady foreign exchange earnings to Uganda, amidst declining volumes of fish exports. Despite decline in fish export volumes from 39,000 metric tons in 2005, to 17,600 tons in 2014, export earnings increased from 104 million to 135 million in the same period. To enable Uganda take advantage of this opportunity, innovations that overcome supply constraints will play a critical role. Statistics from NaFIRRI suggest that floating cage technology is a more productive system in comparison to capture fishery. A farmer using floating cage technology produces 12 times more tonnage per annum than counterparts practicing capture fishery - 48 metric tons of fish per annum, compared to only 4 metric tons. To increase fish production, therefore, the adoption of floating fish cage farming technology needs to be scaled up as opposed to continued dependence on capture fishery systems that are less productive and cannot meet the increased demand for fish exports. This brief also draws policy lesson from China and Egypt - the most successful and leading aquaculture producing countries – who made deliberate investments in aquaculture technology and support services, which increased fish farming productivity and exports.